Merkers vir ’n eietydse prakties-teologiese ekklesiologie - Schoeman, Willem J. (Verbum et ecclesia, 2014)
Markers for a contemporary practical theological ecclesiology. Faith communities, especially congregations, are defined and described in a number of ways. Congregations are, for example, more than the working ability of the minister or the financial contributions of its members, but these two aspects are sometimes directly or indirectly used to define a congregation. The demand for a practical theological ecclesiology requires a specific description of a congregation that is more than the abovementioned aspects. The contextualisation of the Christian faith challenge congregations to play a missional role in the community and society. Moral-ethical challenges, the lack of a critical public presence and serious social problems constitute an imperative for the reconsideration of the role of congregations. Empirical research suggests that congregations are mostly working with an ‘own’ internal agenda. Not enough attention, and sometimes little attention, is being paid to matters beyond the congregational boundaries. Is this a sound ecclesiology? This article aims to propose guidelines along which a relevant contextual and practical theological ecclesiology can be developed.